Solution to Challenges Faced by Teachers in Distance Learning to Improve the Quality and Accessibility of Education - Battsetseg Semjaan; Tungalagtuya Khuukhenduu; Munkhtuya Lkhagvasuren (Lavai)
In recent years, Mongolia has been paying great attention to the development of new knowledge-based industries, contributing to the development of the social, economic, and education sectors. One of the quality reforms being made to prepare a modern Mongolian citizen is the quality and accessibility of distance education. In particular, operations to meet this goal are developed and implemented in coordination with the financing mechanism. Alongside with government organizations, international, non-governmental, and civil society organizations play significant roles for achieving the goals that described above. The objectives of this study were (i) to support the discovery and sustainability in the field of education and distance learning, (ii) the quality and equal access to education due to geographical location, socio-economic conditions, and differences of development in learning. Exploring opportunities lost and how these losts relate to gender, ethnic minorities, remoteness, and the challenges facing teachers in managing online and distance learning. We are going to reflect on the results of quantitative research in the paper, including the experiences of teachers who provided educational services during the pandemic. The study explores the possibility of implementing distance learning in the general education sector in the future, measuring its interrelationships with national and local indicators. Based on data from 225 teachers from 45 schools nationwide, conclusions and solutions have been developed.